Modelling of finances of Vilnius University - Eidukevičius, Rimantas; Ivanauskas, Feliksas; Pikturna, Aleksas (Lietuvos matematikos rinkinys, 2008)
The dynamics of Vilnius university budget, professors and students is presented. The model consists of three discrete time equations. The parameters were estimated and the solutions exhibit nonstable behavior what suggests necessity of external intervention.